Does long term residency near industry have an impact on the body burden of polychlorinated dibenzo-p-dioxins, furans, and polychlorinated biphenyls in older women?. Issue 12 (18th November 2005) - Pless-Mulloli, T; Edwards, R; Howel, D; Wood, R; Paepke, O; Herrmann, T
Abstract : Background: For the retrospective study of environment and health linkages biomarkers of exposure are required. Polychlorinated dibenzo-dioxins and furans (PCDD/F) and polychlorinated biphenyls (PCBs) have been useful markers in some settings. This is the first study of PCDD/F body burden in a population based sample from the UK. Aims and Methods: The authors aimed to investigate whether long term residents close to a heavy chemical industrial complex (Teesside, UK) had a higher body burden and distinct pattern of PCDD/F and PCBs. We measured current levels of PCDD/F and PCBs in a population based sample of older women (mean 64 years, range 42–79 years). Forty women were recruited, 20 living near (zone A: 0.1–2.7 km) and 20 distant (zone C: 5–40 km) from industry during 2000–03. The authors ascertained occupational exposure to lung carcinogens, residential history, consumption of local produce, breast feeding, diet, and height and weight. Results: The mean body burden measured on lipid basis in ng/kg for the whole sample was: WHO-TEQ (PCDD/Fs): 29.9, 2378TCDD: 4.0, PCB 118:16200, PCB156: 13100. Body burdens were similar to others reported from industrialised countries, except that mean 2378TCDD was slightly higher. Mean ages, body mass index, and lifelong dietary patterns were similar in both zones. The authors found no significant difference in mean body burden levels between zones A and C before or after adjustment for covariates. All congener patterns were consistent with an urban background pattern, and there was no significant difference between congener compositions in the two zones. The TCDD body burden increased with age with accelerated increments above age 70. Conclusion: Long term residency near heavy and chemical industry did not have an effect on women's body burden of PCDD/Fs and PCBs on Teesside, UK. The body burden of PCDD/F and PCBs was not a suitable biomarker for chronic, non-occupational exposure to industrial air pollution.